Tn5-directed cloning of pqq genes from Pseudomonas fluorescens CHA0: mutational inactivation of the genes results in overproduction of the antibiotic pyoluteorin. - Schnider, U (1995)
Pseudomonas fluorescens CHA0 produces several secondary metabolites, e.g., the antibiotics pyoluteorin (Plt) and 2,4-diacetylphloroglucinol (Phl), which are important for the suppression of root diseases caused by soil-borne fungal pathogens. A Tn5 insertion mutant of strain CHA0, CHA625, does not produce Phl, shows enhanced Plt production on malt agar, and has lost part of the ability to suppress black root rot in tobacco plants and take-all in wheat. We used a rapid, two-step cloning-out procedure for isolating the wild-type genes corresponding to those inactivated by the Tn5 insertion in strain CHA625. This cloning method should be widely applicable to bacterial genes tagged with Tn5. The region cloned from P. fluorescens contained three complete open reading frames. The deduced gene products, designated PqqFAB, showed extensive similarities to proteins involved in the biosynthesis of pyrroloquinoline quinone (PQQ) in Klebsiella pneumoniae, Acinetobacter calcoaceticus, and Methylobacterium extorquens. PQQ-negative mutants of strain CHA0 were constructed by gene replacement. They lacked glucose dehydrogenase activity, could not utilize ethanol as a carbon source, and showed a strongly enhanced production of Plt on malt agar. These effects were all reversed by complementation with pqq+ recombinant plasmids. The growth of a pqqF mutant on ethanol and normal Plt production were restored by the addition of 16 nM PQQ. However, the Phl- phenotype of strain CHA625 was due not to the pqq defect but presumably to a secondary mutation. In conclusion, a lack of PQQ markedly stimulates the production of Plt in P. fluorescens.